Treatment of acute respiratory distress syndrome in secondary surfactant deficiency in neonates - Heru Samudro; Winarno Winarno (Indonesian Pediatric Society, 2007)
In this report we present data of three premature infants who received 1 to 2 doses of surfactant for an acute respiratory deterioration and after initial surfactants treatment for RDS.